The Ability of a Charophyte Alga Hexokinase to Restore Glucose Signaling and Glucose Repression of Gene Expression in a Glucose-Insensitive Arabidopsis Hexokinase Mutant Depends on Its Catalytic Activity - Ulfstedt, Mikael; Hu, Guo-Zhen; Eklund, D. Magnus; Ronne, Hans (Frontiers in Plant Science, 2018)
Hexokinases is a family of proteins that is found in all eukaryotes. Hexokinases play key roles in the primary carbon metabolism, where they catalyze the phosphorylation of glucose and fructose, but they have also been shown to be involved in glucose signaling in both yeast and plants. We have characterized the Klebsormidium nitens KnHXK1 gene, the only hexokinase-encoding gene in this charophyte alga. The encoded protein, KnHXK1, is a type B plant hexokinase with an N-terminal membrane anchor localizing the protein to the mitochondrial membranes. We found that KnHXK1 expressed in Arabidopsis thaliana can restore the glucose sensing and glucose repression defects of the glucose-insensitive hexokinase mutant gin2-1. Interestingly, both functions require a catalytically active enzyme, since an inactive double mutant was unable to complement gin2-1. These findings differ from previous results on Arabidopsis AtHXK1 and its orthologues in rice, where catalytic and glucose sensing functions could be separated, but are consistent with recent results on the rice cytoplasmic hexokinase OsHXK7. A model with both catalytic and non-catalytic roles for hexokinases in glucose sensing and glucose repression is discussed.